Konsep akal Menurut Perspektif Alquran dan Para Filsuf - Firdaus M. Yunus; Syamsul Rijal; Taslim HM Yasin (Ar-Raniry: International Journal of Islamic Studies, 2020)
This study aims to examine the position of reason in the Quran and philosophers point of view. As a qualitative study, research uses data from reading material available in libraries. The materials obtained were analyzed systematically so that the data could be justified. Intellect has a function of thinking and a tool to examine everything that is needed by humans. Reason as a reflection of the human rational soul has special powers that are not possessed by plants and animals. Human reason not only has rational power, it also has elements of "malakuti" and Divine, because in the mind there is soul and spirit. As a spiritual organ, and also the heart (qalb) it is very possible for humans not only to communicate with spiritual beings, but also to navigate the attributes of prophets, angels and divinities that are not possible by any creation in this world.